2016
DOI: 10.1038/nbt.3468
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mapping of regulatory DNA

Abstract: Quantifying the effects of cis-regulatory DNA on gene expression is a major challenge. Here, we present the multiplexed editing regulatory assay (MERA); a high-throughput CRISPR/Cas9-based approach that analyzes the functional impact of the regulatory genome in its native context. MERA tiles thousands of mutations across ~40 kb of cis-regulatory genomic space and uses knock-in green fluorescent protein (GFP) reporters to read out gene activity. Using this approach, we obtain quantitative information on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
196
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(204 citation statements)
references
References 49 publications
8
196
0
Order By: Relevance
“…2C and SI Methods). Furthermore, we found that REPTILE predictions recaptured the most distal regulatory DNA elements that were identified by multiplexed editing regulatory assay (MERA), a high-throughput genome mutation screening approach (38) (Fig. S2C and SI Methods).…”
Section: Reptile Shows Superior Prediction Accuracy Compared With Eximentioning
confidence: 99%
“…2C and SI Methods). Furthermore, we found that REPTILE predictions recaptured the most distal regulatory DNA elements that were identified by multiplexed editing regulatory assay (MERA), a high-throughput genome mutation screening approach (38) (Fig. S2C and SI Methods).…”
Section: Reptile Shows Superior Prediction Accuracy Compared With Eximentioning
confidence: 99%
“…2a). These reagents can bypass the epigenetic constraints of gene expression within a cell and have been used for a variety of genomewide screens to efficiently silence either single or multiple genes or silence the influence of regulatory domains in the native genomic context 49, 50, 51, 52, 53, 54, 55, 56, 57, 58.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…This suggests that the RFN system might be better suited than SpCas9 for assays where larger deletions are beneficial, such as for interrogating gene-regulatory elements (e.g., distal enhancers and promoters), which might not be greatly influenced by single base deletions. 25,26 Finally, we analyzed whether changing the linker peptide had any influence on the cleavage site. To address this, we plotted the raw reads containing indels for our various on-target sites ( Figure S6).…”
Section: Off-target Analyses Reveal Unaltered High Fidelity Of Rfn Vamentioning
confidence: 99%
“…Although they have tested a broad range of spacer distances (0-30 bp) to target GFP in a GFP stable cell line, actually only a few spacing distances showed activity (14-17 and 26 bp). In contrast, Guilinger et al 17 tested a set of variants with 12 different fusion linkers, but compared them only at a small set of gRNA spacing combinations (5,10,14,20,25,32, and 43 bp), of which most did not reveal any functionality. It remained unclear why most variants performed poorly and/or lacked activity, and also what influence the fusion linkers might have over the full spectrum of gRNA spacing possibilities.…”
Section: Introductionmentioning
confidence: 99%